Upper oesophageal gastric heterotopia: a prospective necropsy study in children. Issue 7 (July 1988) - Variend, S; Howat, A J
Abstract : Three hundred specimens of oesophagus obtained at necropsy from infants and children aged from 0 to 14 years, dying from a variety of causes, were examined prospectively for evidence of gastric heterotopia. Gastric heterotopia was observed in 63 (21%) of the whole series, representing a much higher incidence than reported previously. Excluding deaths in the perinatal period, the incidence appeared to be inversely related to age. Heterotopia was restricted to the subcricoid level of the oesophagus and often showed a close association with lymphoid tissue. There was no association with congenital malformation, and heterotopia occurred more commonly in those infants whose deaths were unexplained, although the reason for this association was unclear.